2015
DOI: 10.1109/tr.2015.2421391
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Securing Networks Using Software Defined Networking

Abstract: Software Defined Networking (SDN) is rapidly emerging as a new paradigm for managing and controlling the operation of networks ranging from the data center to the core, enterprise, and home. The logical centralization of network intelligence presents exciting challenges and opportunities to enhance security in such networks, including new ways to prevent, detect, and react to threats, as well as innovative security services and applications that are built upon SDN capabilities. In this paper, we undertake a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(66 citation statements)
references
References 49 publications
1
64
0
1
Order By: Relevance
“…The survey found that SDN security is still at its nascent stage. Similar studies have been performed by Wenjuang et al [13], Ali et al [20], Scott-Hayward et al [19] and Chen et al [24]. Moreover, Kreutz et al [14] strongly advocated for the importance of integrating security and dependability into SDN design and outline various threats categories which SDN can be attacked with such as, forged traffic flows, attacks on vulnerabilities in controllers and switches, attacks on control plane communication, lack of trust between controller and management applications and so on.…”
Section: Related Worksupporting
confidence: 86%
See 1 more Smart Citation
“…The survey found that SDN security is still at its nascent stage. Similar studies have been performed by Wenjuang et al [13], Ali et al [20], Scott-Hayward et al [19] and Chen et al [24]. Moreover, Kreutz et al [14] strongly advocated for the importance of integrating security and dependability into SDN design and outline various threats categories which SDN can be attacked with such as, forged traffic flows, attacks on vulnerabilities in controllers and switches, attacks on control plane communication, lack of trust between controller and management applications and so on.…”
Section: Related Worksupporting
confidence: 86%
“…This is because, threats emanating from cyber activities are growing exponentially and more sophisticated where the potential impact of a successful attack on network like the SDN may be catastrophic [20]. Thus, it is critically essential that various SDN security threats should be attended to at the early stage in order to reap the benefits it offers.…”
Section: B Sdn Security and Trustmentioning
confidence: 99%
“…The implementation of the firewall rules in Mininet with POX Controller proves the ability to generate policies by mining the logs. This work can be extended to derive the firewall policy with respect to attack detection using ensemble algorithm and mine the associated firewall rules whereas switch itself will act as an Intrusion Detection System [12].…”
Section: Resultsmentioning
confidence: 99%
“…This poses unique challenges for management framework designer of IoT. Research on security management can be found in [15].…”
Section: Security Managementmentioning
confidence: 99%